Estudo numérico do isolamento térmico de painéis do sistema Light Steel Framing em situação de incêndio - Marcos Ferreira de Souza (2010)
The Light Steel Framing building system has been used on a large scale and its application is becoming more popular in Brazil. This work presents a numerical study of heat transfer in models of wall panels for this building system. The study analyzes the heat transfer through different wall thickness when subjected to high temperatures, the variation and distribution of heat, and the thermal insulation afforded by the materials. The models were developed considering the steel profile and different board configurations, with their respective boundary conditions and properties at elevated temperatures. The wall panelsconstituting materials were altered by using one or two gypsum boards on each side, and the use, or not, of insulating material, rock wool inside the wall. Different types of protection were developed for cold-formed steel using parts of gypsum board. The samples were analyzed via the finite element method and the models were subjected to standard fireand to natural fire exposure. The study founds that adding a second board makes the temperature increase along the wall section has a significant reduction, making the time required for fire resistance over 120 minutes, with the thermal insulation. The use of insulation to fill the cavity leads to higher values of temperature, in the cold-formed profile on the side exposed to fire, due to the low thermal conductivity of rock wool. The study also founds that the different types of protection developed for the steel profile proved quite satisfactory, leading to a significant temperature reduction.